Enhancing the SWAT model for simulating denitrification in riparian zones at the river basin scale. (July 2017) - Hoang, Linh; van Griensven, Ann; Mynett, Arthur
Abstract: Riparian zones have significant impact on nitrate removal despite their small areas. Most research on riparian zones have been implemented at small scales. Direct measurement at large scale is infeasible, thus using models is a good alternative. This study introduces a modified SWAT model, referred as SWAT_LS. Two modifications were implemented: (i) adding hydrological routing from upland areas to riparian zones; and (ii) adding a module to simulate denitrification in riparian zones based on the Riparian Nitrogen Model. SWAT_LS was applied to the Odense river basin in Denmark, a densely tile-drained agricultural river basin. Compared to SWAT, SWAT_LS provides an equally good performance for streamflow, and a significant improvement in nitrate predictions. SWAT_LS predicts that current riparian zones remove only 4–17% of nitrate loads because 70% of the riparian areas are bypassed due to subsurface drainage implementation. This ability would dramatically increase to 25–85% if riparian zones are entirely undrained. Highlights: In SWAT_LS, upland areas can interact with riparian zones and denitrification is simulated by the Riparian Nitrogen Model. SWAT-LS provides an equally good performance for streamflow with SWAT2005. SWAT_LS obtains a significant improvement in nitrate predictions in comparison with SWAT2005. The nitrate removal capacity of riparian zones in the Odense river basin is currently 4–17%, but can reach 25–85%.